Faktor Yang Mempengaruhi Kepatuhan Perawat Dalam Kelengkapan Pengisian Berkas Rekam Medis Di RS X - Anugraini, Sulfianti Dewi; Kurniawan, Afif; Wijaya, Hermanto (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2025)
Background: According to Minister of Health Regulation no. 30 of 2019, a hospital is a health service institution that provides inpatient, outpatient and emergency care. The growth of the middle class population in Indonesia increases the need for health services, as well as triggering competition between hospitals at home and abroad. The quality of hospital services is greatly influenced by the performance of medical personnel, infrastructure and efficient work systems. Complete medical records and stored for at least five years for document ownership and patient identification. Aims: This study used a cross-sectional design to investigate the factors that influence nurses' compliance in filling out medical record files (BRM) at Hospital X Surabaya. By creating hypotheses and research questions, finding research variables, determining research subjects, taking measurements, and analyzing data. Results: Logistic regression test, category 1 shows a high value, the extrinsic value has a significant value of 0.215, with a value of Exp(B) = 4.925, and a value of 0.215 is greater than 0.05. So the results obtained are extrinsic values ​​that do not affect nurses' compliance when they fill out medical records. The logistic regression test shows that Category 1 shows a high value, and the intrinsic value variable shows a significant value of 0.215. The conclusion of this research is that nurses' compliance is not directly related to the completeness of BRM filling, although BRM completeness is still important for providing effective care and as a source of information for hospital management